Le code criminel et les unions ouvrières (Relations industrielles / Industrial Relations, 1956)
Pour l'intérêt de nos lecteurs, nous avons cru intéressant de reproduire les articles 409, 410, 411, 365, 366 et 367 du code criminel relatifs aux unions ouvrières. C'est un extrait du chapitre 51 des Statuts annuels du Canada, 1953-54.

Le Congrès du Travail Canadien (Relations industrielles / Industrial Relations, 1956)
Un article de la revue Relations industrielles / Industrial Relations, diffusée par la plateforme Érudit.

Livres reçus [v. 11, no. 2 (1956)] (Relations industrielles / Industrial Relations, 1956)

Livres reçus [v. 11, no. 3 (1956)] (Relations industrielles / Industrial Relations, 1956)

Livres reçus [v. 11, no. 4 (1956)] (Relations industrielles / Industrial Relations, 1956)

Publications récentes [v. 11, no. 2 (1956)] (Relations industrielles / Industrial Relations, 1956)
Bibliography with subject headings.

Publications récentes [v. 11, no. 3 (1956)] (Relations industrielles / Industrial Relations, 1956)
Bibliography with subject headings.

Publications récentes [v. 11, no. 4 (1956)] (Relations industrielles / Industrial Relations, 1956)
Bibliography with subject headings.

La stabilité de l'emploi — L'expérience des textiles - Berry, W. M. (Relations industrielles / Industrial Relations, 1956)
Dans l'industrie du textile, les variations saisonnières et cycliques se font particulièrement sentir au niveau de l'emploi et conséquemment un chômage assez considérable en résulte. L'auteur, avant d'étudier ces problèmes, situe cette industrie dans le cadre général industriel de la Province et cite certains chiffres et faits significatifs; il s'arrête ensuite au chômage proprement dit, à ses causes et conséquences et termine en dégageant quelques conclusions et en suggérant quelques moyens d'assurer une certaine stabilité de l'emploi dans ce secteur.

Disability Retirement in Industrial Pension Plans - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the booklet, "Disability Retirement in Industrial Pension Plans," by W. Michael Blumenthal. Published by the Industrial Relations Section, Princeton University (62 pages).

Effective Personnel Selection Procedures - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the book, "Effective Personnel Selection Procedures," by C. Harold Stone and William E. Kendall. .

Formal Job Evaluation and Some of Its Economi[c] Implications. Research Report No. 1. - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the booklet, "Formal Job Evaluation and Some of Its Economi[c] Implications," by L. G. Nicolopoulos. Research Report No. 1. Published by the Industrial Relations Centre, McGill University (43 pages).

Handbook of Industrial Engineering and Management - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the book, "Handbook of Industrial Engineering and Management," edited by W. Grant Ireson and Eugene L. Grant.

Industrial Conflict and Dispute Settlement. Seventh Annual Conference (April 18-19, 1955). Industrial Relations Centre, McGill University. - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the booklet, "Industrial Conflict and Dispute Settlement. Seventh Annual Conference (April 18-19, 1955). Published by the Industrial Relations Centre, McGill University (121 pages).

Keeping Pace with Automation. Special Report No. 7. - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the book, "Keeping Pace with Automation. Special Report No. 7." Published by the American Management Association. New York (136 pages).

Money and Motivation : An Analysis of Incentives in Industry - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the book, "Money and Motivation : An Analysis of Incentives in Industry," by William F. Whyte et al.

Municipal Labour Relations in Canada - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the booklet, "Municipal Labour Relations in Canada," by S. J. Frankel and R. C. Pratt. Published by the Industrial Relations Centre, McGill University and Canadian Federation of Mayors and Municipalities (87 pages).

Personnel Management and Industrial Relations - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the book, "Personnel Management and Industrial Relations," 4th edition, by Dale Yoder.

Psychology of Personnel in Business and Industry - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the book, "Psychology of Personnel in Business and Industry," 2nd edition, by Roger M. Bellows.

Sixth Annual Conference (April 21-22, 1954). Industrial Relations Centre, McGill University, - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the mimeograph, "Sixth Annual Conference (April 21-22, 1954)" issued by the Industrial Relations Centre, McGill University (125 pages).

The Sociology of Industrial Relations : An Introduction to Industrial Sociology - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the book, "The Sociology of Industrial Relations : An Introduction to Industrial Sociology," by John B. Knox.

The Union Member Speaks - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the book, "The Union Member Speaks," by Hjalmar Rosen and R. A. Hudson Rosen.

Union Strike Votes : Current Practice and Proposed Controls - Chartier, Roger (Relations industrielles / Industrial Relations, 1956)
The article reviews the booklet, "Union Strike Votes : Current Practice and Proposed Controls," by Herbert S. Parnes. Published by the Industrial Relations Section, Princeton University (141 pages).

La mise-à-pied met-elle fin à l'emploi ? - Cholette, Gaston (Relations industrielles / Industrial Relations, 1956)
Voici une étude préparée au sujet d'un cas particulier qui apporte, dans une large mesure, une réponse d'ordre général à une question de grande importance théorique et pratique : la mise-à-pied met-elle fin à l'emploi ? L'auteur, après avoir reconstitué les faits et exposé la position de l'employeur et du syndicat concernés, donne son opinion à la lumière du droit commun, du droit statutaire et de la convention collective particulière.

Le partage des profits à la Compagnie Supreme Aluminum Industries Ltd. - Cholette, Gaston (Relations industrielles / Industrial Relations, 1956)
La participation des travailleurs aux profits dans les entreprises connaît une grande publicité et fait l'objet de maintes discussions. L'auteur, en observateur sympathique mais objectif, a voulu étudier de près le fonctionnement d'un plan particulier. Les résultats de ses recherches sont une invitation à la prudence dans l'appréciation des formules concrètes qui sont présentées.

Jobs and Workers in India - Dion, Gérard (Relations industrielles / Industrial Relations, 1956)
The article reviews the booklet, "Jobs and Workers in India," by Oscar Ornati. Published by the Institute of International Industrial and Labor Relations, Cornell University.

Le Syndicalisme dans une société libre - Dion, Gérard (Relations industrielles / Industrial Relations, 1956)
Dans une civilisation industrielle et démocratique, le syndicalisme apparaît, comme une institution normale et indispensable. Fruit de la démocratie, il contribue au maintien et au développement de la vie démocratique. A condition cependant qu'il soit lui-même une institution représentant vraiment les travailleurs et leur permettant d'y exprimer leurs aspirations tout en sauvegardant leurs intérêts économiques et professionnels. La démocratie syndicale apparaît comme une exigence indispensable au bien de toute la nation. C'est d'abord la responsabilité des chefs syndicaux de la réaliser par des institutions adéquates et par leur contribution à la formation civique des syndiqués.

Profit-Sharing for Small Business - Dion, Gérard (Relations industrielles / Industrial Relations, 1956)
The article reviews the booklet, "Profit-Sharing for Small Business," by J.J. Kehring. Published by the Profit Sharing Foundation, Evanston (53 pages).

Trade Unions in a Free Society - Dion, Gérard (Relations industrielles / Industrial Relations, 1956)
In an industrial and democratic civilization, labor unionism appears as a normal and essential institution. Born of democracy, it helps to preserve and develop democratic life. There is, however, an essential condition. It must be itself an institution that really represents the workers and gives them the opportunity of expressing their aspirations while safeguarding their economic and professional interests. Union democracy is a necessity for the national welfare. But, above all, democracy in the labor movement is the direct responsability of union leaders who must ensure its maintenance and survival through good institutions and also by their cooperation in the civic education of the rank-and-file members.

L'automation — incidences socio-économiques - Faucher, Albert (Relations industrielles / Industrial Relations, 1956)
L'automation relève des sciences de la nature et des sciences de l'homme à la fois. Dans cet article, l'auteur s'applique à montrer que l'automation, envisagée comme problème humain, ou par rapport à ses conséquences probables sur la société en général, et sur les travailleurs en particulier, soulève des opinions variées, parfois contradictoires. Il propose un cadre de discussion, qui permette de tenir compte du plus grand nombre d'opinions possibles et il situe l'automation dans la chaîne historique des innovations.

[L'ancienneté et les salaires] - Gagné, Jean-H. (Relations Industrielles / Industrial Relations, 1956)
Dans la présente chronique nous rapporterons quelques décisions arbitrales concernant les sujets suivants : l'ancienneté et les salaires.

[Rétroactivité décrétée de la part des unions et des compagnies; griefs concernant l'application de conventions collectives] - Gagné, Jean-H. (Relations Industrielles / Industrial Relations, 1956)
La présente chronique rapporte des extraits de sentences arbitrales et de décisions judiciaires récentes concernant les questions suivantes : rétroactivité décrétée de la part des unions et des compagnies; griefs concernant l'application de conventions collectives

[Un important point de droit] - Gagné, Jean-H. (Relations Industrielles / Industrial Relations, 1956)
Dans la présente chronique, nous référons à un jugement rendu par la Cour Supérieure du district de Saint-François (Sherbrooke) qui selon nous, décide d'un important point de droit.

[Un jugement de la Cour Supérieure en matière de retenue de cotisations syndicales.] - Gagné, Jean-H. (Relations Industrielles / Industrial Relations, 1956)
Dans la présente chronique, nous rapporterons spécialement un jugement de la Cour Supérieure en matière de retenue de cotisations syndicales.

Après dix ans d'apprentissage dans l'industrie de la chaussure - Girard, Léonce (Relations industrielles / Industrial Relations, 1956)
La Commission d'Apprentissage de l'Industrie de la Chaussure dont l'auteur de cet article en est le secrétaire expose les résultats obtenus après dix ans de travaux : 4,800 élèves et employés suivent des cours — formation d'opérateurs — d'ouvriers qualifiés et des cadres.

Psychology in Management - Giroux, C.-R. (Relations industrielles / Industrial Relations, 1956)
The article reviews the book, "Psychology in Management," by Mason Haire.

La grève de l'amiante. En collaboration - Guérin, Raymond (Relations industrielles / Industrial Relations, 1956)
The article reviews the book, "La grève de l'amiante," edited by Pierre Elliott Trudeau.

The Newfoundland Woods Labour Board - Gushue, R. (Relations industrielles / Industrial Relations, 1956)
In this article, the author intends to give to the reader a good idea of the Newfoundland Woods Labour Board. After a short description of the situation leading to its formation, he exposes its organization, development and continuance under several chairman; he also presents an interesting composition of the woods labour rates and working conditions in 1940 and 1955 and some activities and accomplishments of the Board. Finally, his analysis of the results of the Board's operations proves that labour and management can effectively co-operate.

The Industrial Mobility of Labor as a Probability Process - Hodgson, James (Relations industrielles / Industrial Relations, 1956)
The article reviews the book, "The Industrial Mobility of Labor as a Probability Process." Isadore Blumen , Kogan Marvin Kogan and Philip J. McCarthy. Cornell Studies in Industrial and Labor Relations, No. VI, Cornell University (163 pages).

Employment Stability: The Private Sector of the Canadian Economy - MacPherson, R. B. (Relations industrielles / Industrial Relations, 1956)
In this article, the author gives a special attention to the problem of employment stability in the private sector of the Canadian economy. Before elaborating this theme, he considers the importance of a growth industry and the problems associated with it; he then suggests some solutions and draws some personal conclusions.

Sur le droit de grève dans les services publics au Canada - Mankiewicz, René H. (Relations industrielles / Industrial Relations, 1956)
Ce rapport étant destiné à s'insérer dans une série d'études sur la grève dans les services publics, le recours à la méthode comparative semble particulièrement utile. Le terme de comparaison sera fourni par les principes généraux admis par les principaux pays européens, notamment la France. L'auteur examine d'abord la catégorie « service public », ce qu'elle comprend et qu'elle couvre; puis, il jette un coup d'oeil sur les « fonctionnaires » ou agents des services publics; il s'arrête enfin au point important de la grève dans ce secteur et amène d'intéressantes distinctions et dégage en dernier lieu quelques conclusions.

Employee Attitude Surveys in the United States - Moore, David (Relations industrielles / Industrial Relations, 1956)
The author first discusses generally the employee attitude survey, describing the techniques commonly used, evaluating the ordinary questionnaire technique with its many drawbacks and limitations; these, however, can be — and have been — gradually corrected with time, and one of them has been refined into an instrument called the SRA Employee Inventory. The rest of the article is spent describing and assessing the Inventory, and finally giving the results and trends in employee attitudes which it has yielded.

Guaranteed Wages, Company Unemployment Benefits and the New Unemployment Insurance Act - Owen, C. F. (Relations industrielles / Industrial Relations, 1956)
The purpose of this article is to continue the study of the factors involved in the possible co-ordination of unemployment insurance with the varied schemes entitled, "Guaranteed Wages", to amplify some of the issues that have been already raised, and to base the analysis on the new Unemployment Insurance Act, which came into operation in October, 1955. Also, special regard will be paid to the principle of the limited financial liability of the company involved in guaranteed wage proposals, and its possible implications for unemployment insurance.

L'Eglise devant les exigences humaines de l'économie - Pape Pie XII (Relations industrielles / Industrial Relations, 1956)
Sa Sainteté Pie XII a fait parvenir par l'entremise de Mgr Dell'Acqua, de la Secrétairerie d'Etat, une lettre à M. Charles Flory, président de la Commission générale des Semaines sociales de France tenue à Marseille. Voici le texte intégral de cet important document.

Les relations humaines du travail - Pape Pie XII (Relations industrielles / Industrial Relations, 1956)

Blind Confidence in Automation - Pope Pius XII (Relations industrielles / Industrial Relations, 1956)
This is the basic theme of a letter addressed to the president and participants of the 43rd French Social Week in Marseilles. It was sent on behalf of Pope Pius XII by Msgr. Angelo Dell'Acqua, Vatican Substitute Secretary of State for Ordinary Affairs.

Codetermination and German Politics - Spiro, Herbert (Relations industrielles / Industrial Relations, 1956)
The author first discusses three forms of codetermination in Germany. He then explains how codetermination came into being in that country, stressing less the ideological factors than the concrete situation which prevailed in Germany after the Second World War. He later describes the actual workings of codetermination in the German iron, steel and coal industries. There follows an evaluation of codetermination by various participants from three viewpoints: economic, sociological, and political.

Les policiers et l'arbitrage - Tousignant, Fabienne (Relations industrielles / Industrial Relations, 1956)
A la suite d'une étude sur l'arbitrage dans les services publics, chez les policiers en particulier, l'auteur livre au lecteur certaines considérations, remarques et conclusions qui s'en sont dégagées. Ce bref aperçu donne une idée de la situation un peu spéciale dans laquelle vivent et travaillent les employés de ce secteur dans la Province de Québec et de ce qui pourrait être fait pour assurer de meilleures relations patronales-ouvrières.